Validation of the French version of the Vulnerable Elders Survey-13 (VES-13) - Belmin, Joël; Khellaf, Lyamna; Pariel, Sylvie; Jarzebowski, Witold; Valembois, Lucie; Zeisel, John; Lafuente-Lafuente, Carmelo (BMC medical research methodology, 2020)
Background Identifying and assessing degree and type of frailty among older persons is a major challenge when targeting high risk populations to identify preventive interventions. The Vulnerable Elders Survey-(VES-13) is a simple instrument to identify frailty defined as risk for death, functional decline or institutionalization. Objective Translate VES-13 into French and validate it. Methods The French version of VES-13 was developed by forward-backward translation of the VES-13 survey instrument. The authors assessed its feasibility, construct validity, and ability to predict the combined outcomes of admission to institution or death at 18 months, in 135 persons over 70 years of age living in the community. Subjects were recruited from three settings: Group 1 – a health prevention center ( n = 45); Group 2 – an ambulatory care geriatric clinic ( n = 40); and Group 3 – an intermediate care hospital unit ( n = 50). The combined outcomes data were recorded by telephone interview with participants or a proxy. Results Feasibility of the French version, named Echelle de Vulnérabilité des Ainés-13 or EVA-13, was excellent. The scale classified 5 (11%) persons as vulnerable (score of 3 or more) in Group 1, 23 (58%) in Group 2 and 45 (90%) in Group 3 ( p < 0.001) with scores of 0.91 +/− 1.16, 4.27 +/− 3.17 and 6.90 +/− 3.17, respectively ( p < 0.001). At follow-up, among the 60 non-vulnerable subjects, 58 (96%) were alive and living at home, whereas 46 (65%) of the 70 vulnerable subjects were alive and living at home ( p < 0.001). Conclusions EVA-13 was determined to be valid and reliable.